Density functional theory study of (110)B-MnO2, B-TiO, and b-VO2, surface in metal - air batteries - Maenetja, Khomotso Portia (My University, 2017)
Density functional theory (DFT) study is employed in order to investigate the surfaces of, β-MnO2, β-TiO2 and β-VO2 (β-MO2) which act as catalysts in Li/Na-air batteries. Adsorption and co-adsorption of metal (Li/Na) and oxygen on (110) β-MO2 surface is investigated, which is important in the discharging and charging of Li/Na– air batteries. Due of the size of the supercell, and assuming that oxygen atoms occupy bulk-like positions around the surface metal atoms, only five values of (gamma) Γ are possible if constraint to a maximum of 1 monolayer (ML) of adatoms or vacancies: Γ= 0 surface is the stoichiometric surface, Γ= 1, 2 are the partially and totally oxidised surfaces, and Γ=-1, -2 are the partially and totally reduced surfaces. The manganyl, titanyl and vanadyl terminated surface is not the only surface that can be formed with Γ= +2. Oxygen can be adsorbed also as peroxo species (O2)2-, with less electron transfer from the surface vanadium atoms to the adatoms than in the case of manganyl and titanyl formation. The redox properties of the (110) surfaces are investigated by calculating the relative surface free energies of the non-stoichiometric compositions as a function of oxygen chemical potential. Increasing the temperature and lowering the pressure (i.e. more reducing conditions) we find the stoichiometric surface reduces first partially and then entirely at higher temperatures. The lithium orientation between two bridging oxygen and in-plane oxygen (bbi) orientation is much more stable for the three metal oxides, thus lithium generally prefers to adsorb where it will be triply coordinated to two bridging oxygens and one in-plane oxygen atom. However, sodium prefers to orientate itself on the bridging oxygen on the surface, but a triple coordination on sodium is also favourable. Oxygen adsorption on Li/MO2 was simulated and it was found that in all ii the metal oxides (MnO2, TiO2 and VO2) the most stable orientation is the dissociated composition where there is an oxygen atom on the “bulk-like” positions on top of each of the M cations. The surface lithium peroxide for MO2 simulated produces clusters with oxygen - oxygen bond lengths that are comparable to the calculated bulk and monomer discharge products reported in literature. Adsorption of oxygen on Na/MO2 was investigated and it was observed that the catalysts used encourage formation of the discharge product reported in literature, i.e. NaO2. The surface NaO2 appears to have comparable bond lengths to the calculated bulk and monomer NaO2.
Thesis (Ph.D. (Physics)) -- University of Limpopo, 2017
Keywords: Density Functional Theory; Batteries; Mathematical physics; Lithium cells; Metals -- Absorption and adsorption